Queer teachers' agency in language education : shaping inclusive and equitable learning environments - Ulla, Mark Bedoya (Emerald points., 2025)
Queer Teachers' Agency in Language Education explores how to create an inclusive, gender-fair language learning environment by embracing the queer identity of the teacher, challenging traditional norms and fostering acceptance. Language teaching is inherently tied to the social and cultural contexts in which it occurs, and it reflects, often unconsciously, the dominant norms and values of society. As such, language classrooms are frequently sites where heteronormative practices and assumptions are reproduced, often to the detriment of queer language teachers and students. Mark Bedoya Ulla delves into the interplay of culture, gender identity, and language in the classroom to cultivate a more inclusive and open learning space and discusses how queer language teachers can actively shape inclusive, equitable language learning environments. Chapters emphasise the importance of queer teachers' roles, identity, and agency in promoting social justice in language education. Through a combination of empirical studies and theoretical discussions, Queer Teachers' Agency in Language Education empowers queer language teachers by highlighting their role as agents of change. It offers strategies to help them challenge heteronormativity in their professional practices and contribute to creating a more inclusive educational environment.